2019
DOI: 10.1159/000502126
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Depression on Poor Glycemic Control in Adults with Type 2 Diabetes: The Mediating Roles of Self-Efficacy and Self-Management Behaviors

Abstract: <b><i>Background:</i></b> High levels of depression and poor self-efficacy and self-management are associated with worse glycemic control, but the linkage and pathway between these variables are poorly understood. We conducted this study to investigate the hypothesis that self-efficacy and self-management mediate the influence of depression on poor glycemic control. <b><i>Methods:</i></b> We studied a purposive sample of 142 adults with type 2 diabetes attending … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…The relationship between empowerment-related constructs and depressive symptoms was reported in thirty-five studies ( n = 9315) ( 34 36 , 47 , 48 , 54 , 55 , 58 , 61 63 , 65 , 66 , 69 , 71 , 73 , 75 , 77 , 78 , 83 , 84 , 86 90 , 92 , 93 , 96 , 105 108 , 110 , 111 ). The most frequently used empowerment construct was self-efficacy ( n = 27) ( 35 , 54 , 55 , 58 , 61 63 , 65 , 66 , 69 , 71 , 73 , 75 , 77 , 78 , 80 , 83 , 84 , 86 90 , 92 , 93 , 96 , 105 , 106 ), followed by patient empowerment itself ( n = 4) ( 34 , 36 , 47 , 48 ), perceived control ( n = 2) ( 110 , 111 ) and patient activation ( n = 2) ( 107 , 108 ). Two studies were not included in the quantitative analysis due the lack of numerical data ( 65 , 83 ) and Sacco et al ( 92 ) was also excluded because its sample...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The relationship between empowerment-related constructs and depressive symptoms was reported in thirty-five studies ( n = 9315) ( 34 36 , 47 , 48 , 54 , 55 , 58 , 61 63 , 65 , 66 , 69 , 71 , 73 , 75 , 77 , 78 , 83 , 84 , 86 90 , 92 , 93 , 96 , 105 108 , 110 , 111 ). The most frequently used empowerment construct was self-efficacy ( n = 27) ( 35 , 54 , 55 , 58 , 61 63 , 65 , 66 , 69 , 71 , 73 , 75 , 77 , 78 , 80 , 83 , 84 , 86 90 , 92 , 93 , 96 , 105 , 106 ), followed by patient empowerment itself ( n = 4) ( 34 , 36 , 47 , 48 ), perceived control ( n = 2) ( 110 , 111 ) and patient activation ( n = 2) ( 107 , 108 ). Two studies were not included in the quantitative analysis due the lack of numerical data ( 65 , 83 ) and Sacco et al ( 92 ) was also excluded because its sample...…”
Section: Resultsmentioning
confidence: 99%
“…Through a MA including thirty correlation coefficients from twenty-nine original studies ( n = 8,990) ( 34 36 , 47 , 48 , 54 , 55 , 58 , 61 63 , 66 , 69 , 71 , 73 , 75 , 77 , 78 , 80 , 84 , 86 90 , 93 , 96 , 105 108 , 110 , 111 ), a weak-to-moderate inverse correlation was found ( r = −0.29; 95%CI −0.33 to −0.24; I 2 = 78.08%; k = 32) ( Figure 5 ).…”
Section: Resultsmentioning
confidence: 99%
“…Studies have also revealed that diabetic patients who had depression, and emotional problems-associated with diabetes, had significantly poorer control of HbA1c [18][19][20]. A study conducted in Iran (2019) showed that depression level was significantly related to glycemic control (HbA1c level) in which the worse the depression level, higher the HbA1c level [21]. Depression could activate adrenergic receptors located on macrophages because it can trigger psychological stress in the brain.…”
Section: Discussionmentioning
confidence: 99%
“…The link between depression and consequently hyperglycemia could be explained by self-management behaviors and self-efficacy. Higher depressive symptoms have been associated with fewer self-management behaviors and low self-efficacy, which has in turn been related to hyperglycemia [ 26 ].…”
Section: Discussionmentioning
confidence: 99%